The Effect of Pond Water Colour, Plankton Diversity, Culture Techniques and Feed Management on Production Characteristics of Vannamei Shrimp Farming in Kerala, India - A.T. Anna; K. Dinesh (Fishery Technology, 2022)
Currently white-legged shrimp, Penaeus vannamei is the most cultured shrimp species worldwide. Vannamei farming has already received immense response from the farmers due to the availability of high-quality specific pathogen-free (SPF) seed, amenability of the species to high stocking density and possibility of high production from the unit area. The pond watercolor, plankton diversity, culture techniques and feed management on production potentialities of the species were evaluated at different stocking densities in the semi-intensive culture system in Kerala, India. Six different stocking rates 15, 25, 30, 40, 50 and 60 nos m-2 designated as T1, T2, T3, T4, T5 including control in triplicates were adopted and reared for a period of 120 days. During the culture period, farmers maintained stable pond watercolour and natural productivity by keen observation employing regular manuring and fertilization. Phytoplankton of the group Bacillariophyta dominated in the majority of the culture ponds followed by Chlorophyta. whereas Copepoda and Rotifera were the major dominated zooplankton groups. The majority of the growth parameters did not show any significant differences except Average Daily Growth (ADG) which showed highly significant differences in both the crops. The findings of this study revealed that natural production in vannamei culture ponds is appeared to be an important source of food and nutrition and also provides good environmental conditions for shrimp cultivation. Moreover, this also helps to reduce the cost of production effectively.